Overview of Deep Dermal Fillers - Liu, Michael H.; Beynet, David P.; Gharavi, Nima M. (Facial Plastic Surgery, 2019)
Dermal fillers have become an integral part of both medical and cosmetic dermatology. Our expanding knowledge of the aging face has allowed us to shift the focus from skin-reduction lifting procedures to soft tissue augmentation. Within the past 5 years alone, nine new dermal fillers have been approved by the U.S. Food and Drug Administration for soft tissue augmentation. The rise in both the use and number of dermal fillers in recent years is a testament to their safety and efficacy. Dermal fillers can be broken down to three major types: temporary, semipermanent, and permanent. The former, which include hyaluronic acid based fillers, provide safe and effective correction but only for a limited time, typically approximately 1 to 2 years at best. This review will cover the semipermanent (poly-L-lactic acid and calcium hydroxylapatite) and permanent (polymethylmethacrylate and liquid silicone) injectable fillers. These so-called deep dermal fillers are valuable, durable tools in correcting the aging face. Given their extended duration of effect, these fillers inherently carry their own risk for potential adverse events. Thus, it is essential that clinicians have a thorough understanding of these products to best counsel, recommend, and perform soft tissue augmentation using these fillers.
Keywords: filler; soft tissue augmentation; semipermanent filler; permanent filler; rejuvenation